PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN BERNYANYI PADA MATA KULIAH KONSEP PENDIDIKAN SENI 1 SD DI STKIP NASIONAL PADANG PARIAMAN - Winda Febrianti Sari (Ensiklopedia Education Review, 2020)
Implementation of character education through learning to sing in the concept of art education 1 SD at STKIP Nasional Padang Pariaman in music, there are 3 meetings for singing material, 1 meeting for material and singing theory and the next meeting is continued with singing practice accompanied by a lecturer, then at the last meeting will be assessed with a practice exam singing with the concept of a choir. Determining the types of songs to be performed is also a way for prospective elementary school (SD) teachers to enrich their compulsory, national and regional songs in Indonesia. By implementing this method, students are familiar with national compulsory songs and regional songs. When the meeting on singing material begins, students will be provided with knowledge about what is vocal, what is singing, how to breathe, articulation in singing, choir and so on. In the next meeting, students will practice in the classroom accompanied by a lecturer. It was only at the next meeting that the practical test of singing was carried out, and the results were very satisfying. The character values shown by students in learning singing in the art education concept course 1 SD At STKIP Nasional Padang Pariaman, there are a lot of them, namely, religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, enthusiasm. nationality, love the homeland and love the archipelago, responsibility and many more.